2013
DOI: 10.1097/scs.0b013e31828607ef
|View full text |Cite
|
Sign up to set email alerts
|

Coil Embolization and Surgical Removal of Carotid Body Paraganglioma

Abstract: Carotid body paraganglioma has considerable malignant potential and locally aggressive behavior, so it should be treated as soon as it is discovered.We report the case of 60-year-old male patient with a carotid body paraganglioma (Shamblin group II) that was causing the carotid arteries to spread. Angiography showed 1 dominant feeding artery arising from the right external carotid artery. Selective angiography was performed 2 days before surgical removal of the tumor, and the feeding artery was successfully em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The main described advantage of preoperative embolization with microcoils is the ability of palpatory detection of them during surgery and the absence of risks of distal embolism [7]. The disadvantages include the high cost of microcoils [28]. In our opinion, microcoils alone (without NAGLEMs) cannot be used for embolization due to the preservation of blood flow through smaller afferents and microcirculatory network, which was well demonstrated by the AVM of the face group and in case #2.…”
Section: Discussionmentioning
confidence: 82%
“…The main described advantage of preoperative embolization with microcoils is the ability of palpatory detection of them during surgery and the absence of risks of distal embolism [7]. The disadvantages include the high cost of microcoils [28]. In our opinion, microcoils alone (without NAGLEMs) cannot be used for embolization due to the preservation of blood flow through smaller afferents and microcirculatory network, which was well demonstrated by the AVM of the face group and in case #2.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have reported various benefits of embolization such as reduction in tumor size, intra-operative blood loss, operative time, reduced complications and hospital stay [11][12][13]. The unique advantage of Microcoil embolization as we have experienced, is the ability to deploy the coil selectively, precisely and proximal to the feeding vessel thereby preventing complications of unwarranted distal embolization [13,14]. Intraoperatively an added advantage is the ability to palpate the coil and it acts as a surgical marker in identifying the feeding vessels [14].…”
Section: Discussionmentioning
confidence: 96%
“…The unique advantage of Microcoil embolization as we have experienced, is the ability to deploy the coil selectively, precisely and proximal to the feeding vessel thereby preventing complications of unwarranted distal embolization [13,14]. Intraoperatively an added advantage is the ability to palpate the coil and it acts as a surgical marker in identifying the feeding vessels [14]. A recent advancement in the endovascular approach to CBPGLs is the use of covered stents for vascular exclusion and studies have shown promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the Shamblin classification has been adopted in only 19 of 60 (32%) of the eligible studies, 11,17,21,23,[25][26][27][28][30][31][32][33][34][35][36][37][38][39] and therefore, the benefit of preoperative embolization in CBTs of the highest size grade has yet to be demonstrated. The size of tumors treated with preoperative embolization and surgical excision was 1.6 to 11 cm, almost the same (range, 2-12 cm) in the patients treated with surgery only (Table IV).…”
Section: Discussionmentioning
confidence: 99%